LABORATORIUM KIMIA VIRTUAL: ALTERNATIF PEMBELAJARAN KIMIA UNTUK MENINGKATKAN HASIL BELAJAR MAHASISWA TADRIS KIMIA IAIN WALISONGO SEMARANG - -, Mulyatun (Jurusan Kimia, Fakultas Matematika dan Ilmu Pengetahuan Alam, Universitas Negeri Semarang, 2013)
The objectives of this study were to describe the efectiveness of using virtual chemistryÂ laboratory to improve the chemistry studentsâ learning. The subjects of this study were theÂ students at grade I of Tadris Kimia IAIN Walisongo Semarang in the academic year ofÂ 2011/2012.The subjects was 40 students. The research uses cluster random sampling technique.Â Class TK-IA is chosen as experimental class (the students who are taught using virtual chemistryÂ laboratory), and class TK-IB is chosen as control class (the students who are not taught usingÂ virtual chemistry laboratory). The result showed that the average score for eksperimental class isÂ 31,4 for the pre test and 74,4 for the post test. While the average for control class is 31,6 for the Â pre test and 62,2 for the post test. The calculation using the t-test showed the value of the t-testÂ is higher than the value of the t-table.the value of t-test is 4,332 while the value oft-table on alphaÂ 5% is 2,02 (4,332>2,02). It can be concluded that there is a significant difference in studentâsÂ learning between students who are taught using virtual chemistry laboratory than students whoÂ are not taught without it. So, we can conclude that using virtual chemistry laboratory is effectiveÂ to improve the chemistry studentsâ learning.